(untitled) (Colombia Medica, 2020)
Introduction: The aim of the study is to assess the functional independence of a group of patients with mucopolysaccharidosis using the Functional Independence Measure as a tool that accomplishes this purpose. Methods: This is a cross-sectional study of patients with mucopolysaccharidosis. Our data was collected between June 2015 and July 2016. In addition to history of present illness and physical examination each study participant was asked to answer a questionnaire to specifically evaluate their functional independence using the Functional Independence Measure. The internal consistency of the Functional Independence Measure was assessed using Cronbach’s alpha coefficient. Results: We collected data on 20 patients with mucopolysaccharidosis. The average age was 10.8 (8.67-13.03) years, the average weight was 23.6 (19,91-27,37) kg and the average height was 1 (0.83-1.17) m. The most prevalent type of mucopolysaccharidosis in the study was type VI (n=14). The average total Functional Independence Measure score was 104.4 (97.61-111.19), the average for the Mobility domain was 73.50 (68.22-78.78) and the average for the Cognitive Function domain was 30.90 (28.68-33.13). The internal consistency of the entire questionnaire was 0.859, with values of 0.966 for the Mobility domain and 0.624 for the Cognitive Function domain. Conclusion: The lowest Functional Independence Measure scores were obtained in the following sub-domains: Self-care, Locomotion and Cognitive Function. The Functional Independence Measure questionnaire demonstrated internal consistency for the evaluation of functional independence in patients with mucopolysaccharidosis, being able to value all the affected sub-domains separately.